The Uses of Pedicled buccal Pad of Fat Flap in Reconstruction of Intra Oral Defects - Alsinibli, Mudher M; Alkhayat, Adil; Al-Anee, Auday M (Journal of Baghdad College of Dentistry, 2016)
Introduction: Different surgical techniques used for closure of various oral defects. While each one of these techniques has its limitation; the buccal pad of fat used in last quarter of last century as pedicle or free graft in reconstruction of small to medium, congenital and acquired defects showed good potentials for success. The present study used the BPF as pedicled flap to reconstruct intra oral defects. The study aimed to evaluate of the success of buccal pad of fat pedicled flap in the reconstruction of intra oral defects. Outlining its indications, limitations and complications. Materials and Methods: The study included 19 patients (17 males and 2 females) with age range between (1- 70 years), all patients were treated with pedicled BPF for intra oral defects (8 pts. with oro-antral communications, 5pts. with maxillary alveolar bone defects, 4 pts. with cleft palate, and 2 pts. with carcinoma of buccal mucosa), under general or local anesthesia. Follow-up period was for 3 months post-operatively, Results:The results showed that 94.7% of patients had complete epithelization of flap and complete closure of the defect within 4-6 weeks. Only 1 pt. 5.3% had total flap loss with very small size of the BPF. In postoperative period, 5.3% of pts. complained from pain, trismus, vestibular obliteration, partial flap loss, all disappeared gradually within 1 month from the reconstruction. Conclusion:The BPF is reliable, easy, safe method to reconstruct small and medium size intra oral defects of maximum size 5x4x3 cm, in maxilla from upper canine region to the soft palate, and in buccal mucosa from retro molar area to the commissure of the mouth. Key words: BPF, intra oral defects, reconstruction.